Mixed-time rolling energy optimization of islanded microgrid considering source-load uncertainty. (October 2019) - Liu, Y L; Miao, S H; Liu, Z W
Abstract: Effective energy optimization means make full use of distributed generation, energy storage and load resources in islanded microgrid, reduce system operation and maintenance costs, and increase the service life of equipment. Based on this, a hybrid rolling energy optimization method for islanded microgrid considering source-load uncertainty is proposed in this paper. Firstly, the source-load uncertainty model based on triangular fuzzy number is established, and the uncertainty programming theory is used to transform the model into a deterministic form. Then, considering the demand-side response, an islanded microgrid energy optimization model based on fuzzy chance-constrained programming is established. On this basis, in order to reduce the dependence of the model on prediction accuracy, a hybrid time division method based on sliding time window is proposed, and an adaptive adjustment method of model confidence is proposed to coordinate the robustness and economy of the model. Finally, an example is given to verify the correctness and effectiveness of the proposed energy optimization strategy.